Asia Pacific Trade Agreement (APTA) - Pranav Pilaniya (International Journal on Economics, Finance and Sustainable Development, 2021)
The Asia-Pacific Trade Agreement (APTA), previously known as the Bangkok Agreement[1] and renamed 2 November 2005,[2] was signed in 1975. It is the oldest preferential trade agreement between countries in the Asia-Pacific region. The APTA covers market for 2921.2 million people [2] which accounts for US$14615.86 billion in terms of gross domestic product (GDP) in the Fiscal Year (FY) 2015-2016.[3] APTA’s key objective is to hasten economic development among the seven participating states opting trade and investment liberalization measures that will contribute to intra-regional trade and economic strengthening through the coverage of merchandise goods and services, synchronized investment regime and free flow of technology transfer making all the Participating States to be in equally winsome situation. Its aim is to promote economic development and cooperation through the adoption of trade liberalization measures. APTA is open to all members of the United Nations Economic and Social Commission for Asia and the Pacific, which serves as the APTA Secretariat. Members of APTA are currently participating in the Fourth Round of Tariff Concessions, which are expected to conclude in October 2009.[4]